PEMANFAATAN BUAH APEL (Malus sylvestris MILL.) LEWAT MATANG SEBAGAI SUBSTRAT NATA DE APPLE - Achmad Gazali; Anita Munawwaroh (Biota, 2017)
Malang and Batu are territories for the apel production in Indonesia. overripe and rejected apples become trash only. So, it’s needed to make a solution for raising value. The reseach was conducted in Mei-Juli 2016, having an object to utilize the overripe apel for making substrates of nata de apple. Apples were gotten from malang apple shop. Samples were washed and mixed with water until 50%:50% of ratio (cider A), after that, filtering cider with a gause. Cider was deluted by watering again until achieving 75%:25% (cider B) and 87,5%:12,5% (cider C) of ratio. All ciders were heated to avoid a bacteria contaminant. 100ml each of cider is put into specific bottles and added with 10-20 ml of Gluconobacter xylinus. The ciders were incubated at room temperature. The result of this study showed that the growth of nata de apple on cider A (1.27 ± 0,9cm) is thicker than B (1.27 ± 0,9cm) and nata on cider B was thicker than C (0.13 ± 0,1 cm). The nata weight was 66.7gr for A, 43gr for B and 4.2gr for C. The residual liquid fermentation test showed that the total acid 0.4 mg/ml for A, 0.3 mg/ml for B and 0.1 mg/ml for C. The sugar reduction degree was 17,15 mg/ml of 32.4 mg/ml for A, 8 mg/ml of 26.4 mg/ml for B, and no sugar reduction of 6.3 mg/ml for C. It could be concluded that the cider A resulting the best subrate of nata de apple..